ANALISIS TERHADAP KEPAILITAN PERSEKUTUAN KOMANDITER DAN AKIBAT HUKUMNYA BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (STUDI KASUS PUTUSAN PENGADILAN NIAGA MEDAN NOMOR : 01/PAILIT/20 - MUHAMMAD REZA (PREMISE LAW JURNAL, 2013)
ABSTRACT The provision in Article 5 of UUKPKPU above is editorially in effect for the request of bankruptcy of a certain company. The regulation of CV is under the control of firm’s problem CV is basically as specified firm, which the specified there’s in the limited partnership whose there’s no in firm . In the firm only there’s ally’s work or Firmant ,whereas in the CV, there is a working ally and also there’s limited partnership or silent ally (sleeping partner). limited partnership is an ally only hand over the money, goods or labor as income on the partnership, while he doesn’t interfere in the management or control of the partnership. But, in practice, many business people use CV as the form of their companies. Therefore, a research on the bankruptcy of a limited partnership is needed in order to give the contribution of science to support the agreement between the foundation and principles in the law of bankruptcy, especially in the bankruptcy of a limited partnership. Keywords: Bankruptcy, Limited Partnership, Legal Consequences